-6k+3=-7-(6k-8)

Simple and best practice solution for -6k+3=-7-(6k-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6k+3=-7-(6k-8) equation:


Simplifying
-6k + 3 = -7 + -1(6k + -8)

Reorder the terms:
3 + -6k = -7 + -1(6k + -8)

Reorder the terms:
3 + -6k = -7 + -1(-8 + 6k)
3 + -6k = -7 + (-8 * -1 + 6k * -1)
3 + -6k = -7 + (8 + -6k)

Combine like terms: -7 + 8 = 1
3 + -6k = 1 + -6k

Add '6k' to each side of the equation.
3 + -6k + 6k = 1 + -6k + 6k

Combine like terms: -6k + 6k = 0
3 + 0 = 1 + -6k + 6k
3 = 1 + -6k + 6k

Combine like terms: -6k + 6k = 0
3 = 1 + 0
3 = 1

Solving
3 = 1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2=2m-2 | | 4x(2x+9)-2(5x+6)= | | 7x+4-3+5-3x= | | 3x-11=-2x-7 | | -16=3-5n+1 | | 18y=6 | | 2*(1200/x) | | 6/m-3 | | 3j-2=14 | | x-6.25=2.5 | | -28x-7y=28 | | 7x+4y-3x+4= | | 13+x(x-13)-(2-5x)=2.8 | | 15d+7=8d+56 | | 19-x=2 | | 3+4j=11 | | -10=-4a-6a | | 3.4=6c-8 | | 2+2r=4 | | 6-2x-1=13 | | 1=5-2t | | 5p=41.5 | | 1.5-0.04x=-0.7 | | 12-5x+5=7-3x+6 | | -48+3x=24-6x | | -3x+12=-10+10 | | 2y(1.7)+x(3.6)=9 | | X+3=.8x+4 | | 38=9c-7 | | 8e-6=50 | | 4x^11=24 | | 7*x=2x+x^2+3(4x)+17 |

Equations solver categories